Optimization of treatment methods for chronic diseases of the nose and paranasal sinuses combined with chronic dacryocystitis - N.J. Khushvakova; F.A. Nurmukhammedov; U.F.Davronov (International Consortium of Education and Culture Research Studies, 2019)
The pathogenesis of the overgrowth of dacryorrhinostoma is based on many factors from the development of granulations and scars in the area of ​​the bone opening to the development of the commissural opening, mucositis in the nasal cavity to purulent persistent forms of rhinosinusitis in the area nose-lacrimal duct. To improve the reparative processes after the operation of endoscopic dacriocystomy with the installation of silicone stent-drainage (from the intubation tube), a zinc hyalrate solution was used.